Degree of knowledge about Linux systems: a study with students of information systems (Revista Brasileira de Contabilidade e Gestão, 2013)
This article aims to identify the degree of knowledge of a group of Information Systems students regarding Linux systems. To that end, we have the quantitative and technical analysis of a questionnaire, carried out with the 2013/1 phase of the Education Center of the Alto Vale do Itajaí, of the Santa Catarina State University. As a result, attesting that this group, with considerable knowledge in the technological areas, sees Linux as a system of intermediate difficulty level is possible.
Keywords: Linux; knowledge; systems; operational systems